2012
DOI: 10.1155/2012/863203
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Work-Focused Supports for People with Severe Mental Illnesses in Australia

Abstract: Persons with severe mental illness (SMI) have reduced workforce participation, which leads to significant economic and social disadvantage. This theoretical review introduces the strategies that have been implemented to address this issue. These include Individual Placement and Support (IPS) services, the most widely researched form of supported employment, to which cognitive remediation has more recently been recognised in the USA, as an intervention to improve employment outcomes by addressing the cognitive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 82 publications
1
6
0
2
Order By: Relevance
“…Findings from previous research have consistently found generally low levels of participation in domestic, employment and social activities for consumers in comparison to the general community, and this remains a stubbornly persistent problem. The employment rate identified in this study (19.58%) is lower than that reported internationally (Becker et al., 2007; Broyd et al., 2016) but is congruent with the rate consistently reported in Australian studies for the past 2 decades (Contreras et al., 2012; Waghorn et al., 2012). As noted by the World Health Organization and Calouste Gulbenkian Foundation (2014), there is a relationship between employment and mental illness that increases their respective negative influences on each other.…”
Section: Discussionsupporting
confidence: 88%
“…Findings from previous research have consistently found generally low levels of participation in domestic, employment and social activities for consumers in comparison to the general community, and this remains a stubbornly persistent problem. The employment rate identified in this study (19.58%) is lower than that reported internationally (Becker et al., 2007; Broyd et al., 2016) but is congruent with the rate consistently reported in Australian studies for the past 2 decades (Contreras et al., 2012; Waghorn et al., 2012). As noted by the World Health Organization and Calouste Gulbenkian Foundation (2014), there is a relationship between employment and mental illness that increases their respective negative influences on each other.…”
Section: Discussionsupporting
confidence: 88%
“…They identify four themes that emerge as challenges to implementation: fear on the part of professionals, individuals and their families that work will have a negative impact on the client, a culture of low expectations, failure to provide the support that is proven to work, and the global recession. Contreras et al (2012) review the research from Australia and New Zealand and maintain that the central challenge for implementing IPS is the incorporation of the vocational assistance into the public mental health services. Boardman (2013) summarizes the research on IPS and possible barriers for implementation and points to clients' motivation, self-efficacy and previous employment history.…”
Section: Introductionmentioning
confidence: 99%
“…Derudover er de teamorienteret og professionelle og effektive ift. administration af deres tid og ressourcer på de forskellige opgaver (Quimby et al 2001, van Erp et al 2007, Koletsi et al 2009, Glover et al 2011, Boardman 2013, Contreras et al 2012, Larson et al 2014). …”
Section: Det Individuelle Niveauunclassified
“…I den internationale forskning er der ligeledes primaert fokus på at generere indsigter i implementeringsprocesserne set fra de professionelles perspektiv. Enkelte studier beskaeftiger sig med deltagernes/brugernes karakteristika og strategier som en faktor, der har indflydelse på IPS indsatsens outcome, og enkelte studier inddrager brugernes erfaringer i forståelsen af de komplekse implementeringsprocesser (Quimby et al 2001,Koletsi et al 2009, Areberg et al 2012, Boardman 2013, Contreras et al 2012, Lexén et al 2013. I den politologiske implementeringsforskning udgør målgruppens adfaerd og interesser et selvstaedigt studieobjekt i forståelsen af implementeringen af offentlig politik (Winther og Lehmann Nielsen, 2008).…”
Section: Brugernes Erfaringerunclassified